2014
DOI: 10.1016/j.applanim.2013.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Cattle behaviours and stockperson actions related to impaired animal welfare at Swedish slaughter plants

Abstract: At a slaughter plant, cattle are sometimes exposed to rough handling which may reduce animal welfare (AW). In an observational study at four Swedish commercial slaughter plants, AW-related behaviours of cattle and actions of abattoir stockpersons handling the same animals were recorded simultaneously. The objective was to estimate the occurrence of different behaviours and actions related to negative AW during driving and stunning at largescale cattle abattoirs, assess associations between such behaviours and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 30 publications
1
54
0
2
Order By: Relevance
“…Slaughter plants are designed based on conventional architectural criteria, such as space optimization or the facilitation of human activities, but do not normally consider the behavioral needs of animals (Miranda-de la . Complete measurements of animal welfare require observations from unloading to unconsciousness, including at the unloading bay, during lairage, moving the cattle to the stun box and at bleeding out (Hultgren, Wiberg, Berg, Cvek, & Lunner Kolstrup, 2014). Reactions to certain aspects of slaughter procedures could have consequences for subsequent slaughter stages, so improving one stage may have positive effects on subsequent stages (Bourguet et al, 2011).…”
Section: Behavioral Indicatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Slaughter plants are designed based on conventional architectural criteria, such as space optimization or the facilitation of human activities, but do not normally consider the behavioral needs of animals (Miranda-de la . Complete measurements of animal welfare require observations from unloading to unconsciousness, including at the unloading bay, during lairage, moving the cattle to the stun box and at bleeding out (Hultgren, Wiberg, Berg, Cvek, & Lunner Kolstrup, 2014). Reactions to certain aspects of slaughter procedures could have consequences for subsequent slaughter stages, so improving one stage may have positive effects on subsequent stages (Bourguet et al, 2011).…”
Section: Behavioral Indicatorsmentioning
confidence: 99%
“…On the other hand, it should be taken into account that both the facilities available during those stages and the handling by the stockpersons will also influence animal behaviour. Several authors suggest the measurement of falls, aggression/fight, slips, jumps, baulks, reversing, mounting and vocalizations (Van de Water et al, 2003;Minka & Ayo, 2007;Bourguet et al, 2011;Hultgren et al, 2014), since they are indicators (events) associated with fear-related behavioral responses and might reflect the efficiency with which the animals are handled upon arriving at the slaughter plant (Hemsworth et al, 2011;Miranda-de la Lama et al, 2012). Loading and unloading conditions will influence the quality of lairage time; however, lairage under poor conditions will also affect animal behaviour.…”
Section: Behavioral Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical scoring systems have been developed for detecting problems during handling (Grandin 1998a;Maria et al 2004;NCBA-BQA Feedlot Audit 2009;Welfare Quality Network 2009;Edwards et al 2010;Hulgren et al 2014). This makes it possible to determine whether handling has improved or become worse.…”
Section: Measurements Of Livestock Handlingmentioning
confidence: 99%
“…In some abattoirs, electric prods are used extensively. and Hultgren et al (2014) found cattle stress reactions to be associated with rough handling at the abattoir. Atkinson et al (2013) evaluated stun quality following stunning with a cartridge-driven penetrating captive bolt gun, and found signs of consciousness indicative of inadequate stun in 6.5% of the cows, steers and calves, and in 17% of the bulls.…”
Section: Transport and Slaughtermentioning
confidence: 99%